Bibliometric Analysis of the Adaptive Strategies of SMEs in the E-Commerce Era - Malvin Dharma Pradipta; Gunawan Santoso; Sudarmiatin; Trisetia Wijijayanti (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The rapid development of digital technology and online marketplaces has transformed the business landscape, compelling small and medium-sized enterprises (SMEs) to adopt adaptive strategies to remain competitive. This study conducts a bibliometric analysis to map the scientific evolution, research trends, and thematic focus related to SMEs’ adaptive strategies in the e-commerce era. Using data extracted from Scopus and Web of Science, the analysis applies performance analysis and science mapping techniques with tools such as VOSviewer and Bibliometrix. Results indicate significant growth in publications since 2015, with research themes dominated by digital transformation, technological adoption, online marketing, innovation capability, and organizational resilience. Cluster mapping reveals four major thematic groups: (1) digital adoption and technology readiness, (2) e-commerce competitiveness and marketing innovation, (3) supply chain agility and operational adaptation, and (4) SME resilience and sustainability. The study highlights increasing interest in integrating digital platforms, enhancing customer engagement, and leveraging data-driven decision-making. These findings provide a comprehensive overview of the intellectual structure and emerging research directions, offering valuable insights for researchers, policymakers, and practitioners in strengthening SMEs’ adaptability in the e-commerce environment.